2019
DOI: 10.1371/journal.pone.0213196
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of acute vertigo diagnosis and treatment practices between otolaryngologists and non-otolaryngologists: A multicenter scenario-based survey

Abstract: Acute vertigo is a common problem in emergency departments. However, clinical strategies of acute vertigo care vary among care providers. The aim of the study was to investigate differences in diagnosis [Dix-Hallpike test, the head impulse, nystagmus, and the test of skew (HINTS) procedure, and imaging modalities] and treatment (pharmacological treatments and the Epley maneuver) by otolaryngologists and non-otolaryngologists in emergency medicine settings. We used a multicenter case-based survey for the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…8.26%). Stroke/TIA-rates among ER patients reported in the literature range between 3.2% up to 18% [2,12,24]. Cerebellar infarctions can present as AVS ("pseudoneuritis").…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8.26%). Stroke/TIA-rates among ER patients reported in the literature range between 3.2% up to 18% [2,12,24]. Cerebellar infarctions can present as AVS ("pseudoneuritis").…”
Section: Discussionmentioning
confidence: 99%
“…Recent work in a Canadian cohort showed that there are major training deficits in final year otolaryngologists with regard to vertigo diagnostic testing, more specifically the bedside head impulse test [16,19]. A survey-based study emphasized interdisciplinary differences between otolaryngologists and non-otolaryngologists with regard to vertigo diagnosis and treatment practices [24]. Interdisciplinary thinking between neurology, ENT, and internal medicine, is much needed not only to appropriately detect, diagnose and treat life-threatening causes of VD, but also with regard to the high number of unspecified diagnoses termed, demanding an interdisciplinary, holistic view of dizzy patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metoclopramide had a similar efficacy to dimenhydrinate in reducing vertigo, nausea and vomiting in an emergency setting [ 245 ]. Metoclopramide (non-specific compound) is commonly prescribed in the management of MD, BPPV, VN, and other forms of vertigo [ 73 ].Metoclopramide is metabolized to mono-de-ethyl-metoclopramide at least in part by CYP2D6 isoform, and possibly CYP1A2 and CYP3A [ 97 ].…”
Section: Methodsmentioning
confidence: 99%
“…11 Unfortunately, researchers still found variations in the management of BPPV among clinicians from different specialties. 17,18 To improve quality of care and clinical reasoning accuracy, evidencebased guidelines have come into clinical practice. 19 A clinical practice guideline (CPG) for BPPV management was developed and recently updated by the American Academy of Otolaryngology, Head and Neck Surgery Foundation (AAO-HNSF).…”
Section: Introductionmentioning
confidence: 99%